DEVELOPMENT OF PROGRAMS FOR DOMESTIC VIOLENCE OFFENDER TO PREVENT REPETITIVE ACTION - Limsakul, Madee; U-naidhamma, Sukit (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were to study the models of working and to develop a program for working with the domestic violence offender to prevent repetitive action. It was an action research that divided into 2 stages as follows: Phase 1 was an in-depth interview with the officers who work with domestic violence, both public and private sectors, the domestic violence offender who have been subjected to behavioral modification and no futher action and family members of perpetrators. Phase 2 was taken data from interviews to draft a program and training community leaders to implement programs, including focus group with community leaders. Total number of research participants were 33 people. The research tools are semi-structured interview and focus group discussion. The research results showed that 1) there were 2 models to work with the domestic violence offender: work by a state agency (court order) and community work (volunteer). 2) The program has the following steps: classification of program participants, orientation and implementation of the program. (knowledge, attitudes and skills.)The experimental results of the program found that the family group, peer group support, and family camp activities support the program participants to see the problem and realize their ability to change the behavior. As well as making family relationships better, emotional control and communication skills improved. The important suggestion is that the implementation of the program is composed of two parts 1) access to the process of the juvenile court, The court may impose conditions on the program 2) Volunteer to join the program. Operated by state agencies, the private sector, community and the related networks.